Ranking food security indicators and metrics in Hawaiʻi: a Delphi approach - Shon, Jason; Miles, Albie (Frontiers in Sustainable Food Systems, 2025)
A comprehensive set of regionally relevant indicators and metrics is crucial for tracking progress in transforming food systems to meet the UN Sustainable Development Goals (SDGs). Household food security, foundational to sustainable, equitable, and resilient food systems, aligns with SDG 2 (Zero Hunger). Policymakers require accurate data to guide decisions, yet a major challenge is developing scientifically sound, participatory, and reproducible approaches for sub-national food system indicators and metrics. This study addresses this need by using the Delphi research method to create a multi-indicator system of both stand-alone and complementary food security metrics specific to Hawaiʻi. Engaging 24 food security experts in Hawaiʻi, with a 58% response rate in the second round, consensus was achieved on 55 of 71 metrics (78%). The U.S. Household Food Security Survey Module (HFSSM) received the highest rating among stand-alone metrics (3.5, SD = 0.8). Complementary metrics were organized within a framework encompassing the four dimensions of food security: availability, access, utilization, and stability. Access metrics received top ratings, including the ‘rate of households below the ALICE threshold’ (4.4, SD = 0.7). ALICE stands for Asset Limited, Income Constrained, and Employed, and refers to households that earn enough to be ineligible for many public assistance programs but not enough to afford basic necessities. Results highlight the need to clarify terminology, address food (in)security misconceptions, develop new metrics for data gaps, and prioritize initiatives like the Supplementary Nutrition Assistance Program (SNAP) that address Hawaiʻi’s high living costs and enhance food access. The participatory, multidimensional metrics model presented here is adaptable to other regions, extending its impact beyond Hawaiʻi.